COMPARATIVE STUDY OF TRADITIONAL AND MODERN TAHFIZ LEARNING: ANALYSIS OF EFFECTIVENESS AND ITS IMPACT ON THE SPEED OF MEMORISATION BY STUDENTS AT MADRASAH ALIYAH ASSA'ADAH - Amirullah, Muhammad Wahyu; Muid, Abdul (Al-Mubin, 2025)
Qur'an memorization education (tahfiz) is an essential element in the Islamic education system aimed at preserving the purity of Allah’s revelation. With the advancement of technology, tahfiz learning methods have evolved from traditional teacher-student interaction models to modern approaches utilizing applications and online platforms. This study aims to analyze the effectiveness of these two methods on the memorization speed of students at MA Assa’adah Bungah Gresik. A descriptive qualitative approach was applied, using observation, in-depth interviews, and documentation for data collection. The findings indicate that the traditional method fosters discipline and emotional bonding between teachers and students, while the modern method provides time and place flexibility but requires stronger self-supervision. This research contributes to the formulation of more optimal tahfiz learning strategies for Islamic edu$cational institutions